Rancang Bangun Sistem Pendukung Keputusan Seleksi Penerimaan Tenaga Kerja Dengan Metode Fuzzy Inference System - Agustin, Yoga Handoko; Cahya Setia Ningrum, Asni (Jurnal Algoritma, 2025)
Advances in information technology have driven significant changes in the recruitment process. Many companies still rely on manual selection, which tends to be time-consuming, subjective, and poorly documented. This study aims to design and develop a web-based Decision Support System (DSS) using the Mamdani Fuzzy Inference System (FIS) method to support the employee selection process. The system is designed with assessment criteria such as GPA, work experience, skills, and test results. Candidate data is processed through the stages of fuzzification, inference, and defuzzification to produce recommendations for the best candidate order. Testing was conducted using black box testing to ensure system functionality and usability testing involving HRD and administrators. The results of the usability test using the System Usability Scale (SUS) method showed an average score of 93.13, which means that the system is excellent, easy to use, and supports objective and efficient workforce selection needs. This study concludes that the application of Mamdani FIS can assist companies in making more measurable decisions. Further development recommendations include integration with machine learning to improve assessment accuracy and the development of a mobile application for greater flexibility of use.